Dictionaries of linguistic terms and their role in teaching the Arabic language at the university level (Journal of Human Sciences, 2023)
The terms represent the keys to knowledge, and they are the milestones in the way of acquiring knowledge. Because knowledge in any type of science is the key to terminology, and given its importance in the educational process; There has become an urgent need for the existence of educational dictionaries, due to their importance in the educational process, as they are the helper for the learner, and the refuge for him if concepts are difficult for him, in understanding new terms, enriching the linguistic outcome of the learner, and expanding his horizon in understanding the various sciences. Therefore, it is necessary to develop educational dictionaries that suit each age stage, and with all levels of the learner's mental, cultural and scientific.This research aims to address the role of terminological dictionaries in the university study, present models of these dictionaries and show their importance in understanding the linguistic lesson.